The politics of praise : influence and authority in John Berryman's poetry - Coleman, Philip (Trinity College (Dublin, Ireland). School of English, 2002)
This thesis is a reappraisal of John Berryman’s achievement that stresses his poetry’s critical agency over and against the prevailing tendency to describe it in narrow confessional terms. Questioning the received view of him as an author of autobiographical self-obsession, it surveys the range of Berryman’s ideological engagements, from The Dispossessed (1948) to Delusions, Etc. (1972), in an attempt to provoke a broader and more engaged sense of his profile to counter the typical academic and popular transmission of Berryman which tends toward a reduction of the worldly possibilities presented by his work. The evolution of what began as an analysis of the Berryman/Yeats relation into an account of the American poet’s cultural politics is outlined in the introduction, w’here Berryman’s unpublished essay “The American Intellectual and the American Dream” (1947) is cited as a central text in this study’s re-negotiation of his place in twentieth- century American poetic history and criticism. The ideological significance of Berryman’s early advocacy of Yeats is examined in more detail in the first chapter, however, where the transadantic site of the Berryman/Yeats relation is interpreted as the ground for an evaluation of Berryman’s interrogation of the authority of American exceptionalism. Including a discussion of the relationship between patrilinear theories of influence and exceptionalist understandings of American literary culture, this chapter provides a framework for the analysis of Berryman’s poetry and its reception offered in subsequent chapters.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin